Orphan Heritable Thoracic Aortic Diseases and Pregnancy. Modern Outlooks and Guidance - S. O. Siromakha (Ukrainian Journal of Cardiovascular Surgery, 2020)
Pregnancy is a period of high risk for all patients with aortic pathology. Heritable thoracic aortic diseases (HTAD) refer to aortopathies with a high risk of formation and dissection of thoracic aortic aneurysm (TAA). HTAD are caused by a mutation of a certain gene. This paper reviews current perceptions of manifestations of rare hereditary diseases of the thoracic aorta during pregnancy and general recommendations for the medical care of these patients. To date, 16 genes (or loci of unidentified genes) are known to be associated with the development of thoracic aortic aneurysm, and since many families with a history of TAA (about 70%) have no pathogenic changes in any of these 16 genes, additional genes associated with HTAD have not yet been identified.In this paper, HTAD are considered which occur (or are identified) quite rare but provide a significant risk for patients, which is significantly increased during pregnancy (multisystemic smooth muscle dysfunction syndrome, Meester Lois syndrome, LOX and PRKG1 genes mutations, vascular Ehlers-Danlos syndrome, mutations in TGFB2, TGFBR1, TGFBR2, SMAD3 loci, Loeys-Dietz syndrome). The article analyzes the frequency of occurrence of the most threatening complication of HTAD – acute aortic dissection – in various syndromes, defines general recommendations for the examination of patients with HTAD, recommendations for conservative treatment of these patients. Recommendations for the patients (especially fertility women) concerning the preventive cardiac surgery are also summarized in the paper. These principles of pregravidary preparation and multidisciplinary medical support during pregnancy are the most effective prophylactic measures for major cardiac events and maternal death. Pregnancy heart team that has been working in Ukraine since 2013 does all its best to organize medical support for every pregnant woman with suspected HTAD. In this context, it is very important to collaborate with general practitioners and genetics to “catch” such patients before they become pregnant or in very early terms. Individualized plan of pregravidary preparation and medical care during pregnancy and delivery should be developed by a multidisciplinary team.